Financing the green transformation: how to make green finance work in Indonesia - Volz, Ulrich (Palgrave Macmillan, 2015)
Explores challenges for developing and emerging economies for enhancing green financing for sustainable, low-carbon investment, looking at Indonesia. Based on surveys in the Indonesian banking and corporate sectors and expert interviews, it devises innovative policy recommendations to develop a framework conducive to fostering green investments, Planetary boundaries and a scarcity of natural resources will require a significant boost of investment into clean and renewable energy and a more efficient use of resources in developing, emerging and advanced economies alike. In this context, the financial sector will have to play a key role in providing 'green finance' for sustainable investment and development. Against this backdrop, this book investigates the challenges for developing and emerging economies in enhancing green financing for sustainable, low-carbon investment, using Indonesia as a case study. Based on surveys in the Indonesian banking and corporate sectors and expert interviews, the book devises innovative policy recommendations for governments to develop a framework conducive to fostering green investments